Pyoenic granuloma with alveolar bone loss - Amitandra Kumar Tripathi; Vivek Kumar; Charanjeet Singh Saimbi; Jolly Sinha (Wolters Kluwer Medknow Publications, 2015)
Pyogenic granuloma is an inflammatory hyperplasia of connective tissue which arises in response to various chronic low grade irritations. It is a tumor like growth of oral cavity and considers being non-neoplastic in nature. It predominantly occurs in the second decade of life in young females and rarely causes significantly alveolar bone loss. This paper present case of a pyogenic granuloma, the size of lesion was unusual large with severe alveolar bone loss in affected site and managed by surgical intervention.